Investigating the Performance of an Ultrasound-Assisted Rotating Packed Bed Reactor for the Enhancement of the Micromixing Efficiency - Mahdi Hefzi Lotfabadi; Mahdieh Abolhasani (Iranian Journal of Chemical Engineering)
The Micromixing plays a key role in the most of industrial processes; enhancing its efficiency is a very important issue. In this study, a typical rotating packed bed (RPB) reactor equipped with the blade packing and high frequency ultrasonic transducers were designed to study the micromixing efficiency using the iodide/iodate reaction. The utilized ultrasonic transducers were ultrasonic atomizer humidifiers with the frequency of 1.7 MHz. Taking advantage of both the controllable high gravitational force and induced effects of the high frequency ultrasound, simultaneously, in a small volume reactor is the novelty of the present work. The effects of different parameters like the rotational speed, volumetric ratio, concentration of acid, ultrasonic power and number of activ transducers were investigated with and without the ultrasonic field. By increasing the rotational speed and volumetric flow, the segregation index decreased and by increasing the concentration of acid and volumetric ratio, the segregation index increased. In all of experiments, the segregation index decreased significantly under the ultrasonic field. Moreover, by increasing the ultrasonic power and number of active transducers the segregation index decreased. The obtained results indicated that the relative segregation index increased up to 41.1 % under the 1.7 MHz ultrasonic field. Therefore, the high frequency ultrasonic waves can intensify micromixing, even in a high efficiency equipment like RPB